2019
DOI: 10.3390/medsci7020016
|View full text |Cite
|
Sign up to set email alerts
|

Integrated FISH, Karyotyping and aCGH Analyses for Effective Prenatal Diagnosis of Common Aneuploidies and Other Cytogenomic Abnormalities

Abstract: Current prenatal genetic evaluation showed a significantly increase in non-invasive screening and the reduction of invasive diagnostic procedures. To evaluate the diagnostic efficacy on detecting common aneuploidies, structural chromosomal rearrangements, and pathogenic copy number variants (pCNV), we performed a retrospective analysis on a case series initially analyzed by aneuvysion fluorescence in situ hybridization (FISH) and karyotyping then followed by array comparative genomic hybridization (aCGH). Of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…A recent study showed that the NIPT performed significantly better in predicting sex chromosome trisomies than monosomy X; which could potentially improve the under detection of sex chromosome aneuploidy in prenatal diagnosis (Xu et al, 2019). The integration of aCGH in prenatal diagnosis has extended its diagnostic scope to include pCNVs (Li et al, 2016; Chai et al, 2019). In this study, aCGH was performed in about one third of total prenatal cases with an ADR of 2.59% for pCNVs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the NIPT performed significantly better in predicting sex chromosome trisomies than monosomy X; which could potentially improve the under detection of sex chromosome aneuploidy in prenatal diagnosis (Xu et al, 2019). The integration of aCGH in prenatal diagnosis has extended its diagnostic scope to include pCNVs (Li et al, 2016; Chai et al, 2019). In this study, aCGH was performed in about one third of total prenatal cases with an ADR of 2.59% for pCNVs.…”
Section: Discussionmentioning
confidence: 99%
“…Confined placental mosaicism is one of the main reasons for the inconsistency between NIPS results and prenatal diagnosis results (Grati, 2016). A reflex FISH test is recommended to confirm chromosome mosaicism when a mosaic pattern is highly suspected (Hultén et al, 2003;Cherry et al, 2017;Wang et al, 2018;Chai et al, 2019). Compared with the FISH results, we found a higher proportion of the 45,X counted by karyotyping.…”
Section: Discussionmentioning
confidence: 56%
“…Compared with karyotyping, CNV detection techniques can test uncultured amniotic fluid cells, thus reducing the influence of cell culture on the mosaic ratio and restrictions of the cell cycle on prenatal diagnosis. However, owing to fluctuations in the fluorescence signal intensity and background noise, CMA has a low sensitivity to a lower proportion of mosaic patterns than karyotype analysis and CNVseq (Chai et al, 2019;Hao et al, 2020). The CMA result of amniotic fluid cell testing for case 840 was inconsistent with that of karyotyping of neonatal peripheral blood; the false negative result of CMA may be caused by the above reasons or tissue-specific chimerism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, there has been signi cant development in laboratory protocols used to diagnose genetic conditions [1]. Each protocol has enabled new and enhanced ways of viewing the human genome [2,3]. Genetic testing is carried out based on the diagnosis and clinical indication which allows for the appropriate method to be selected.…”
Section: Introductionmentioning
confidence: 99%